States or markets ? neoliberalism and the development policy debate - Colclough, Christopher (ed.); Manor, James (ed.) (Oxford, 1993)
This volume examines the usefulness of neo-liberal theory and prescriptions for tackling problems in developing countries, ranging through agriculture, industry, education, and health. It considers the impact of neo-liberal theory on the poor and on women, and assesses the neo-liberal record on trade, and financial and structural adjustment problems.
Keywords: Economic development